Production of Bovine Collagen Hydrolysate with Antioxidant Activity; Optimized by Response Surface Methodology - Babak Pakbin; Samaneh Allahyari; Shaghayegh Pishkhan Dibazar; Wolfram Manuel Brück; Roghayeh Vahidi; Razzagh Mahmoudi; Ali Khanjari (MDPI AG, 2022)
Antioxidants are widely used in pharmaceutical industries. Gelatin is a byproduct of the meat industry and its hydrolysates showed several functionalities, such as antioxidant activity. The purpose of this study was to describe and optimize the enzymatic hydrolysis conditions including time, temperature, pH, and enzyme/substrate ratio (E/S) to produce protein hydrolysate with antioxidant functionality from bovine gelatin by RSM; the scavenging activity was evaluated using the DPPH method. The model observed was fitted with desirable adequacy and sufficiency. We found that the antioxidant activity increased significantly (p < 0.05) with the increase in pH value, E/S ratio, and time of enzymatic process; however, the temperature had no significant (p < 0.05) effect on the antioxidant activity of the hydrolysate. The optimum hydrolysis conditions were observed at a temperature of 35.3 °C, pH of 8.0, and E/S ratio at 2.5 after 2 h hydrolysis by trypsin enzyme. The results showed that the hydrolysate under these conditions, optimized by RSM, could be more effective on antioxidant activity. Regarding the antioxidant potential, gelatin hydrolysate can be used as an antioxidant supplement in pharmaceutical industries.